Spiritual Education from the Perspective of the Qur'an - Shifwah Salsabila Zahira; Husnul Qodim (UIN Sunan Gunung Djati Bandung, 2021)
This research aims to discuss the education of spiritual perspectives of the qur'an. These research methods are qualitative through library studies with a qualitative approach. The results and discussions of this research include an understanding of education, the value of the spiritual perspective of Islam, and the spiritual education in the qur'an. The study concluded that education did not escape from the object of the education itself and thus give humans a distinct potential from other creatures.